2009
DOI: 10.1179/174367609x414017
|View full text |Cite
|
Sign up to set email alerts
|

Chemically formulated ceramic gamma ray irradiation shielding materials utilising red mud

Abstract: Novel shielding materials for electromagnetic radiations have been formulated using two different approaches using red mud and processed red mud based systems. The crystallographic aspect of multicomponent and multishielding phases, in the formulated shielding materials, on the shielding efficiency has been studied. The formulated shielding materials have been evaluated for radiation attenuation using Co-60 gamma ray irradiation source and were found to reduce the shielding thickness, i.e. half value thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 25 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Red mud is a by-product of aluminum production from bauxite. It contains a high percentage of TiO 2 , Fe 2 O 3 , and Al 2 O 3 at 20.32–21.2%, 31.88–32.33%, and 7.3–8.5%, respectively [ 98 ]. The ceramic form of red mud is produced as a radiation shielding material through sintering and combination with BaCO 3 or BaSO 4 .…”
Section: Alternative Materials Used In Rscmentioning
confidence: 99%
“…Red mud is a by-product of aluminum production from bauxite. It contains a high percentage of TiO 2 , Fe 2 O 3 , and Al 2 O 3 at 20.32–21.2%, 31.88–32.33%, and 7.3–8.5%, respectively [ 98 ]. The ceramic form of red mud is produced as a radiation shielding material through sintering and combination with BaCO 3 or BaSO 4 .…”
Section: Alternative Materials Used In Rscmentioning
confidence: 99%
“…[8][9][10][11] Furthermore, ceramic shielding materials against c-ray irradiation by utilising red mud was also reported. 12 The objective of this study is to develop low cost EMI clay based ceramic building products using metallurgical EAFS and LFS as admixtures, maintaining also the required technological and environmental specifications.…”
Section: Introductionmentioning
confidence: 99%
“…Although many investigations have been carried out over the recent years for the development of fired ceramic bricks containing metallurgical slags and wastes as admixtures, only a few studies have been reported regarding the EMI shielding effectiveness of clay based ceramic building products 811. Furthermore, ceramic shielding materials against γ -ray irradiation by utilising red mud was also reported 12…”
Section: Introductionmentioning
confidence: 99%